The Effect of Physical Exercise on Students' Level of Attention and Distress - Welly , Wise; Cassy , Marbun Ribka; Karundeng, Miracle Jade Edith; Vania, Syenell Angel; T , Truong; C, Cañesares (12th International Scholars Conference 2025, 2026)
Physical exercise has been proven to be associated with attention and distress. However, there is no research has yet been done to show that physical activity has a direct impact on both attention and distress. This study aims to determine if there is a significant effect of physical exercise on the students' level of attention and distress. There were three treatments or interventions utilized in this study: physical exercise for 10 minutes, 5 minutes, and no exercise at all. The Kessler Psychological Distress Scale (K10) was used to evaluate the level of distress of the participants, and the Sustained Attention to Response Task (SART) was used to measure the level of attention of the participants. Thirty (30) undergraduate students from various nationalities in Adventist University of the Philippines were selected and were randomly assigned into 3 treatment groups: 10 minutes group (n = 10), 5 minutes group (n = 10), and no exercise group (n = 10). They were given the task to do the pre-test and post-test before doing the interventions. Between-subject experimental design was utilized, and the data from the K-10 Psychological Distress Scale and the SART Test were analyzed using the paired sample t-test, and One-Way ANOVA statistics were also used to analyze the SART Test results. Results revealed that, the no physical exercise intervention did not have significant effect on the distress level (t=2.02, df=9, p=.074), the same as with the 5-minutes physical exercise intervention that showed no significant effect on the distress level (t = 0.836, df= 9.00, p = .425), while the 10-minutes physical exercise intervention showed that there is a significant effect on the distress level (t9= 2.64, p=.027). Also, the control group and the 5-minute physical exercise intervention did not show any significant difference, while the 10-minute physical exercise showed that there is a significant effect on the level of attention (t9= 3.4, p=.008). Results implied that 10-minute physical exercise is a very effective way to reduce the distress level compared with having only 5-minute physical exercise or no exercise at all. In addition, the 10-minute physical exercise is the only intervention that can improve the attention level. It is recommended to replicate the same concept of the experiment to different age groups and perhaps with a different amount of time in the physical exercise intervention with a greater number of participants.